Stay-at-home and face mask policy intentions inconsistent with incidence and fatality during the US COVID-19 pandemic - Wu, Samuel X.; Wu, Xin (Frontiers in Public Health, 2022)
During the COVID-19 pandemic, many states imposed stay-at-home (SAH) and mandatory face mask (MFM) orders to supplement the United States CDC recommendations. The purpose of this study was to characterize the relationship between SAH and MFM approaches with the incidence and fatality of COVID-19 during the pandemic period until the 2020-08-23 (about 171 days), the period with no vaccines or specific drugs had been finished phase III clinical trials yet. States with SAH orders showed a potential 50~60% decreases in infection and fatality during SAH period (about 45 days). After normalization to population density, there was a significant 44% increase in fatality rate in no-SAH + no-MFM states when compared to SAH + MFM. However, many results in this study were inconsistent with the intent of public health strategies of SAH and MFM. There were similar incidence rates (1.41%, 1.81%, and 1.36%), and significant differences in fatality rates (3.40%, 2.12%, and 1.25%. p<0.05) and mortality rates (51.43, 34.50, and 17.42 per 100,000 residents. p<0.05) among SAH + MFM, SAH + no-MFM and no-SAH + no-MFM states, respectively. There were no significant differences in total positive cases, average daily new cases, and average daily fatality when normalized with population density among the 3 groups. This study suggested potential decreases in infection and fatality with short-term SAH order. However, SAH and MFM orders from some states policies probably had limited effects in lowering transmission and fatality among the general public. At the policy-making level, if contagious patients would not likely be placed in strict isolation and massive contact tracing would not be effective implement, we presume that following the CDC’s recommendations with close monitoring of healthcare capacity could be appropriate in helping mitigate the COVID-19 disaster while limiting collateral social-economic damages.